The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1037/a0024138
|View full text |Cite
|
Sign up to set email alerts
|

The effects of age on the strategic use of pitch accents in memory for discourse: A processing-resource account.

Abstract: In two experiments, we investigated age-related changes in how prosodic pitch accents affect memory. Participants listened to recorded discourses that contained two contrasts between pairs of items (e.g. one story contrasted British scientists with French scientists and Malaysia with Indonesia). The end of each discourse referred to one item from each pair; these references received a pitch accent that either denoted contrast (L+H* in the ToBI system) or did not (H*). A contrastive accent on a particular pair … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 65 publications
(117 reference statements)
2
27
0
Order By: Relevance
“…It was possible that memory regarding one proposition (e.g., whether the British or French scientists found the monkey) could be influenced by whether the key word related to the other proposition (whether the monkey was found in Malaysia or Indonesia ) was emphasized. However, a preliminary analysis indicated that this variable had no effect, consistent with past data from young adults on font emphasis (e.g., Lorch et al, 1996) and on pitch accents (Fraundorf et al, 2010; but see Fraundorf, Watson, & Benjamin, 2012, for differing results in other populations, including older adults). Consequently, we collapsed across this variable for all subsequent analyses.…”
Section: Resultssupporting
confidence: 78%
“…It was possible that memory regarding one proposition (e.g., whether the British or French scientists found the monkey) could be influenced by whether the key word related to the other proposition (whether the monkey was found in Malaysia or Indonesia ) was emphasized. However, a preliminary analysis indicated that this variable had no effect, consistent with past data from young adults on font emphasis (e.g., Lorch et al, 1996) and on pitch accents (Fraundorf et al, 2010; but see Fraundorf, Watson, & Benjamin, 2012, for differing results in other populations, including older adults). Consequently, we collapsed across this variable for all subsequent analyses.…”
Section: Resultssupporting
confidence: 78%
“…Prosodic prominence might actually reflect facilitation summed with deliberate choices on the part of the speaker between different forms, or prosodic prominence in other situations might purely reflect categorical choices. Speakers might choose, for instance, between accented forms and deaccented forms to indicate whether information is new to the discourse versus already given in the discourse (Dahan, Tanenhaus, & Chambers, 2002; Pierrehumbert & Hirschberg, 1990; Schwarzchild, 1999; Selkirk, 1995, 2002; Steedman, 2002), or between different accented forms to denote new versus contrastive information (Fraundorf, Watson, & Benjamin, 2010, 2012; Pierrehumbert & Hirschberg, 1990; Selkirk, 1995, 2002; Steedman, 2002). Facilitation-based accounts also do not preclude prosodic prominence being a useful cue for listeners, as has been observed in language comprehension experiments (e.g., Dahan et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…However, other research indicates that older adults can use memory strategies effectively when those strategies are naturalistic (Castel, 2008; Dunlosky & Hertzog, 1998; Fraundorf et al, 2011; Rahhal, May, & Hasher, 2002; Rendell & Craik, 2002; Tentori, Osherson, Hasher, & May, 2001; Tullis & Benjamin, 2011). As described above, the shifts in the type of information that was encoded from the two different study contexts can be thought of as being similar to a study strategy.…”
Section: Discussionmentioning
confidence: 99%